Daily usage of mobile phone among UiTM Pasir Gudang students - Sa’aidon, Ammarhaziq; Azlie, Muhammad Syamel; Ramzi, Nurin Amni; Zulfadzli, Nor Shahila; Alimon, Nur Idayu (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The use of smartphone among university students in the 21st century is seen as an important part of their life because of its advanced features. Students use their smartphones to accomplish their various daily tasks. Reviews from various studies revealed that students utilize smartphones for various purposes. This study focuses on determining the activity prioritize, average time spent per day, amount of bills that they pay and addiction behaviour towards mobile phones. The sample of the study is 64 UiTM Pasir Gudang students. This study also review the relevant literature on smartphone usage pattern among students and identify the positive and negative effect of smartphone on students by focusing on education, psychology and social aspect. This study found that most of the students utilize smartphones for entertainment, social and education purposes. Therefore, the review of this study is important in providing the outcome of smartphone use time spent, bills usage, and the factor addicting towards mobile phones.